Occupational pesticide exposure and respiratory health: a large-scale cross-sectional study in three commercial farming systems in Ethiopia - Negatu, Beyene; Kromhout, Hans; Mekonnen, Yalemtshay; Vermeulen, Roel (Thorax, 2017)
RationaleIn the last decade, due to expansion of greenhouses and irrigated farms, the use of pesticides in Ethiopia has increased 6–13-fold leading to potential health risks.ObjectiveTo investigate if occupational exposure to pesticides is associated with respiratory health effects in farmers and farm workers from commercial farming systems.MethodsWe performed two cross-sectional surveys comprising different farming systems. In the first survey we studied respiratory symptoms among 1104 subjects of which 601 were occupationally exposed to pesticides (ie, 256 pesticide applicators, 345 re-entry workers) and 503 unexposed individuals. The second survey, carried out 2 years later in the same farming regions, additionally included lung function measurement and comprised a total of 387 study subjects of which 206 were occupationally exposed to pesticides (142 applicators and 64 re-entry workers) and 180 unexposed individuals.ResultsWe observed increased risks for chronic cough and shortness of breath (OR=3.15, 95% CI 1.56 to 6.36 and OR=6.67, 95% CI 2.60 to 17.58) among the exposed subjects as compared with unexposed individuals in the first survey. These results were corroborated in the second survey where we also observed reductions in FEV1 (140 mL), forced expiratory flow 25%–75% (550 mL/s) and risk of FEV1/FVC ratio <0.8 (OR=4.31, 95% CI 2.11 to 8.81) among pesticide exposed workers.ConclusionsThese findings indicate an increased risk of adverse respiratory health among workers exposed to pesticides. As those effects occurred in young workers (mean age 27 years) and within a relative short duration of exposure (4 years) implementation of stringent occupational health measures are warranted.